A dynamic warm up programme reduces knee and ankle injuries among youth male sub-elite football players - Asgari, M.; Jaitner, T. (British Journal of Sports Medicine, 2021)
Background: Dynamic exercises appear to be more practical in preventing football-related injuries. Objective: To evaluate effects of a dynamic warm up programme including dynamic stretch, strength and plyometric exercises (DSP) on prevention of injuries. Design: Prospective non-randomized controlled trial. Setting Competitive level. Interventions: Two volunteer teams of Iranian U21 league were assigned to control (n=29,18.5±1.2) and DSP (n=25,18.7 ±1.5) groups. Over a football season (2018), the DSP performed the specific warm up lasting 15 min three times weekly with a progression of intensities over time. The control group followed its routine warm up including football drills and physical warm ups without a specific prevention approach. Injuries and time exposure were recorded according to the FIFA consensus statement. Data were analysed by Chi- Square Test while the level of significant was set as p £0.05. Main Outcome Measurements: Injury incidence and risk ratio for ankle and knee. Results: In total, 7020 h of training and competition and 37 lower extremity injuries were recorded; about 65% in the control group. The injury incidence for DSP and control were 1.8 and 3.4 respectively. Incidences of knee and ankle injuries for DSP and control were 1.0, 0.9, 2.3 and 1.3, respectively. The risk ratio for knee and ankle injuries was higher in the control group by 2.3 and 1.5 times, respectively. Chi-square testing indicated a significantly lower knee injury incidence for the DSP group (p=0.03). Despite a 30% lower injury incidence, the difference of ankle injuries between the groups was not significant (p=0.52). Conclusions: Applying DSP as regular warm up significantly reduced the incidence of knee injuries in youth footballers, which is assumed to be due to a better stimulation of the control mechanisms of the postural system followed by performing the programme. For the ankle, exercises that are more specific should be applied though the limited small sample size may also affect the results.